61.2k views
5 votes
Write a recursive rule for the sequence. 7, 6, 13, 19, 32, ...

User Nocnokneo
by
5.9k points

1 Answer

1 vote

Answer:

recursive rule for the given sequence:


a_n = a_(n-1)+a_(n-2) for n > 2

Explanation:

Given the sequence:

7, 6, 13, 19, 32, ......

then;

First term
(a_(1)) = 7

Second term
(a_(2)) =6

third term
(a_(3)) = 13 and so on..

You can see that:


a_3 = a_1+a_2 = 6+7 = 13

similarly for:


a_4 = a_2+a_3 = 6+13 = 19 and so on..

The recursive rule for this sequence is:


a_n = a_(n-1)+a_(n-2) for n > 2

User AlexTheo
by
5.9k points